INFLUENCE OF DIFFERENT TESTING POSTURES ON HAND GRIP STRENGTH - Walaa M. El-Sais; Walaa S. Mohammad (European Scientific Journal, ESJ, 2014)
Hand grip strength (HGS) is a useful, functional measure of the integrity of upper extremity, however many studies examined it from selected positions (supine, sitting, standing), with no emphasis on other derived positions that are used in a clinical setting. The objective was to evaluate HGS in different body positions that are used in a clinical setting by using a standard protocol. A convenience sample of 40 healthy male participants was recruited for this study, with no history of psychiatric or neurological dysfunction, or upper extremity orthopedic dysfunction. Grip strength was measured in the dominant hand with Jamar Plus+ digital hand dynamometer in five positions: supine, prone, side-lying, sitting and standing. The HGS value in the prone position was significantly lower than that in standing position (p = 0.043) and the sitting position (p = 0.013). However, no statistical difference was found in HGS among supine, prone, side-lying positions. Grip strength correlated moderately with age (r = 0.643). This study provides a useful evaluation of grip strength in different positions. Using identical upper extremity positions, grip strength is variable among different body positions. Grip strength is equivalent when tested from the supine, side-lying or prone, thus position can be adjusted according to the patient's condition. Finally, Age is one of the important determinants of the hand grip evaluation, particularly when standing position is used.